Study on Development of Composite Hydrogels With Tunable Structures and Properties for Tumor-on-a-Chip Research - Chen, Zaozao; Wang, Fei; Zhang, Jie; Sun, Xiaowei; Yan, Yuchuan; Wang, Yan; Ouyang, Jun; Zhang, Jing; Honore, Tess; Ge, Jianjun; Gu, Zhongze (Frontiers in Bioengineering and Biotechnology, 2020)
A major factor for developing new tumor models is to recreate a proper three-dimensional environment for 3D tumors culture. In this 3D microenvironment, extracellular matrices play important roles in regulation of hallmark features of cancer through biochemical and mechanical signals. The fabrication of a mechanical and biophysical controllable hydrogel, while sharing similarities with Matrigel in cancer invasiveness evaluation, is an urgent but unmet need. In this study, we developed a hybrid hydrogel system composed of GelMA and hydrolyzed collagen to model tumor micro-environment and tested with several cancer cells with different origin and characteristics. The hydrogel possesses a well-organized, homogenous microstructure with adjustable mechanical stiffness and excellent permeability. This hydrogel demonstrated similar properties as Matrigel in tumor spheroids culture and 3D tumor invasiveness studies, it was further applied in a Tumor-on-a-Chip system with 3D-bioprinting. Our research demonstrated this hydrogel’s effectiveness in tumor 3D culture, and its potential to replace Matrigel in cancer invasiveness evaluation.